Multistep Finite Volume Approximations to the Transient Behavior of a Semiconductor Device on General 2D or 3D Meshes (Journal of Computational Mathematics, 2007)
In this paper, we consider a hydrodynamic model of the semiconductor device. The approximate solutions are obtained by a mixed finite volume method for the potential equation and multistep upwind finite volume methods for the concentration equations. Error estimates in some discrete norms are derived under some regularity assumptions on the exact solutions.